Increased heat and drought stress under climate change and their impact on physiological growth and development of crops: A review - TIWARI, GIRJA SHANKER; PAREEK, NAVNEET; RAVERKAR, KIRAN P (The Indian Journal of Agricultural Sciences, 2018)
Abiotic stresses are major constraints to crop production and food security worldwide, the increasing trend and projection under climate change pose further challenge and warrants close attention of researchers and policy makers. Heat and drought are judged as most common stresses having adverse impact on growth and productivity of the crops. Understanding of the physiological, biochemical, and ecological responses of these stresses is prerequisite to develop management practices. The plant responses to these stresses can be categorized into morphological, physiological, and biochemical responses quantified to assess their impact. Though plants have capability to modify their growth pattern and physiological process to cope with heat and drought stresses but it costs dearly in terms of overall performance and yield, therefore it is a must to understand plant response to various stresses in order to develop suitable adaptation strategies. This review focuses on the plant responses towards heat and drought stresses pointing on the commonalities and differences. Due to physical damages, physiological disruptions, and biochemical changes under limited water supply and elevated temperatures there is negative impact on crop growth and yields. Both conventional and modern approaches are desired to deal with heat and drought stresses. A holistic approach including short term strategy comprising management practices promoting in-situ moisture conservation, water harvesting, micro environment modification etc, and long term strategies including developing heat and drought tolerant varieties, developing irrigation infrastructure, permanent change in land configuration, etc are required. The recent government. initiative like PMKSY aiming irrigation to each field (Har Khet Ko Pani) through water harvesting, conveyance, drip irrigation in the back drop of time bound target of doubling farmers income will be a big boost to cope heat and drought stress and to induce climatic resilience.